Baseline Values of the Compensatory Reserve Index in a Healthy Pediatric Population - Rodriguez, Salvador A.; Morgan, Gareth J.; Lara, Claudia; Zablah, Jenny E. (Pediatric cardiology, 2022)
The objective of this study is to describe the compensatory reserve index (CRI) baseline values in a healthy cohort of healthy pediatric patients and evaluate the existing correlation with other physiological parameters that influence compensatory hemodynamic mechanisms. CRI is a computational algorithm that has been broadly applied to non-invasively estimate hemodynamic vascular adaptations during acute blood loss. So far, there is a lack of baseline values from healthy individuals, which complicates accurately estimating the severity of the hemodynamic compromise. Additionally, the application of this technology in pediatric populations is limited to a few reports, highlighting a marked variability by age, weight, and other physiological parameters. The CRI of 205 healthy subjects from 0 to 60 years of age were prospectively evaluated from January to February 2020 at several public outpatient clinics in El Salvador; vital signs and sociodemographic data were also collected during this period. After data collection, baseline values were classified for each age group. Multiple correlation models were tested between the CRI and the other physiological parameters. CRI value varies significantly for each age group, finding for patients under 18 years old a mean value lower than 0.6, which is currently considered the lower normal limit for adults. CRI presents strong correlations with other physiological variables such as age, weight, estimated blood volume, and heart rate ( R > 0.8, R 2 > 0.6, p < 0.0001). There is significant variability in the CRI normal values observed in healthy patients based on age, weight, estimated blood volume, and heart rate.